La falta de disposición expresa que regule el término para contestar la demanda en el procedimiento voluntario vulnera la seguridad jurídica - Zambrano Yaruqui, Xiomara Elizabeth (2024)
The voluntary procedure in Ecuador is a legal figure that has been established for certain legal matters in which the interested parties require a judicial resolution in order to enforce their rights, within the general rules of the voluntary procedure recognized in the General Organic Code. of Processes, a verification is carried out regarding due process, in the guarantee of the right to defense, the legal security of the provisions contained and the right to effective judicial protection that originates from this procedure. In the same way, it should be indicated that the voluntary procedure, in the legal field, refers to a specific category of legal processes that are characterized by their non-litigious nature andby the absence of conflict between the parties involved. Unlike contentious procedures, where there is a conflict to be resolved and the intervention of the court is required to make a decision on the dispute, voluntary procedures focus on the processing of matters in which there is no controversy, but rather the need to obtain judicial approval or authorization for certain acts or situations. In the present socio-legal investigation, it is sought to determine if the provisions of the General Organic Code of Processes in relation to the voluntary procedure and in the figures of inventory and accountability have a term or a judicial or legal term for the interested parties to appear before the court. process, this in view of the right to defense that assists every citizen and specifically in the time they must have to prepare an adequate defense. Likewise, in this thesis it is reviewed whether there is a violation of constitutional rights due to the possible lack of an express term or term to answer the demand or appear in the voluntary process, for which several documentary, informative and field techniques have been used. that have served to develop the proposed research topic. In the same way, in this thesis certain categories are presented that help to understand what a voluntary procedure is and it is compared with international legislation in order to establish certain similarities and differencesthat become the legal update that is intended to be proposed.